Physico-chemical, Antioxidant Properties and Sensory Attributes of Golden Melon (Cucumis melon L)-Watermelon (Citrullus lanatus) Juice Blends - Mopeloa Ajoke Sodipo; Adenike Temitope Owolabi; Timilehin David Oluwajuyitan (Archives of Current Research International, 2019)
This study investigates the physico-chemical, antioxidant properties and sensory attributes of golden melon-watermelon fruits juice blends. The juice extracted from golden melon and watermelon fruits were mixed together in different ratios 100% watermelon (GMW 1), 100% golden melon (GMW 2), 50% golden melon and 50% watermelon (GMW 3), 70% golden melon and 30% watermelon (GMW 4), 30% golden melon and 70% watermelon (GMW 5) in order to establish possible synergetic effect. The proximate composition of the samples ranged from 92.07 – 93.91%; 0.49 – 0.81%; 1.83 – 4.91%; 1.80 – 3.62% for moisture content, total ash, crude protein and carbohydrate respectively. The pH of the fruit juice blends ranged from 5.40 to 5.48. There is no significant difference (p<0.05) among the fruits juice samples. The mineral composition of the fruit juice for sodium (Na), potassium (K), iron (Fe), and calcium (Ca) ranged from 17.01 to 41.76 mg/100 g, 9.26 to 38.51 mg/100 g, 0.38 to 1.88 mg/100g, and 3.49 to 8.96 mg/100g respectively. The result shows that the total phenolic content ranged from 6.32-10.20 mg GEA/ 100 g; total flavonoid ranged from 0.08-0.13 mg QAE/ 100 g; DPPH ranged from 55-80%; ABTS ranged from 0.022-0.025 mmol. TEAC/ 100 g and FRAP ranged from 1.20-4.23 mg AAE/g. The results of sensory attributes of the fruit juice revealed that, fruit juice GMW 5 was the most preferable in aroma, taste and overall acceptability by the panelist. Hence, golden melon-watermelon fruit juice blends may serve as a source of strong antioxidant property that may be used to improve health status.